Large falcine meningioma presented as treatment resistant depression : A case report - Sim, Sze Kiat; Khairul Aizad, Bin Adzman,; Lim, Swee San; Wong, Albert Sie Hieng (Malaysian Medical Association, 2019)
Large intracranial tumour may present only with psychiatric symptoms without any neurological deficits. Delay in surgical treatment may significantly affect the quality of life in these patients. We report a case of a young engineering student who was diagnosed as treatment-resistant depression without initial neuroimaging study. Further neuroimaging studies revealed he has a large falcine meningioma. His psychiatric symptoms resolved following surgical resection of the tumour. We emphasized the importance of initial neuroimaging study in young patients presenting with psychiatric symptoms.